MENYELAMATKAN ANAK MASUK PENJARA MELALUI PENDAMPINGAN Studi Kasus Di Provinsi Lampung - Alit Kurniasari (Puslitbangkesos Kementerian Sosial RI, 2009)
Prisoning of a child is the last place for child in court, but cases of children in jail despite mild cases still found. Assistance for children in conflict with the law (ABH) is important, especially in legal and psychosocial aspects, starting when the children were arrested, and after the children had faced the legal process because it is never too late to save the children from being sentenced to jail. The evidence suggests that the impact of the imprisonment of children has more negative than the good results. Result of assistance from NGOs in the province of Lampung, in fact can ensnare adult perpetrators who had been